PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA GOODFELLAS RESTO AND BAR SEMARANG - Heri Ardhianto, 13.05.51.0110 (Students Journal of Economic and Management, 2017)
This study aims to examine the effect of Product Quality, Service Quality, and Price Perception on Purchase Decision. Population in this research is consumer of Goodfellas Resto and Bar Semarang. Samples were taken as many as 100 respondents using non probability sampling technique with purposive sampling approach. Data were collected using survey method through questionnaires filled by consumers. Technique of analysis using multiple regression method previously tested the validity and reliability test. In addition, this study also used the F statistical test and the coefficient of determination. The last test is hypothesis using t test. The results showed that the variable of Product Quality, Service Quality, and Price Perception have positive and significant influence to Purchase Decision. Keyword: Product Quality, Service Quality, Price Perception, and Purchase Decision